The shadow of enlightenment optical and political transparency in France, 1789-1848 - Levitt, Theresa (Oxford : Oxford University Press, 2009)
This work examines the intersection of science and politics in the work of Francois Arago and Jean-Baptiste Biot, the principle architects of the optical revolution of early 19th-century France. Their disagreement over the optical accessibility of the world played out across a wide range of French culture.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Optical engineering -- France -- History -- 18th century; Optical engineering -- France -- History -- 19th century; Enlightenment; France -- Politics and government -- 18th century; France -- Politics and government -- 19th century